Turned - Kenner, Julie (New York : Ace Books/Berkley Pub. Group, 2010)
"With her cover as a double agent inside the forces of evil blown, Lily has no choice but to go underground. She takes along a cadre of warriors: humans, angels, demons, and other trusted creatures. Their only hope is to stop those who are planning to use the Ninth Gate as a wedge that will unleash the fury of hell. But even as they attempt to stop the unholy rituals, they are confounded at every turn by their foes. With the fate of all life on earth in her hands, Lily must confront the hatred within her own soul and uncover a traitor in her midst--and closer to her heart than she ever could have imagined..."- -p. [4] of cover.
Keywords: Demonology -- Fiction; Supernatural -- Fiction; Good and evil -- Fiction; Fantasy fiction